Uji Kandungan Fenol Dan Flavonoid Ekstrak Daun Seligi (Phyllanthus Buxifolius) Dengan Pelarut Etanol Dan Etil Asetat - Sunarmi, Sunarmi; Suhendriyo, Suhendriyo; Tri Ambarwanto, Sigit (Universitas Pahlawan Tuanku Tambusai, 2024)
Seligi leaves are traditionally used to treat sprains and reduce joint pain. The content of phenolic and flavonoid compounds in Seligi leaves also plays a role in its anti-inflammatory activity. Generally, phenolic and flavonoid compounds are soluble in polar and semi-polar solvents. This study aims to determine the levels of phenolic compounds and flavonoids in Seligi leaf extract. Seligi leaf simplicia was powdered with a fineness of 80 mesh and then extracted by maceration method using 96% ethanol and ethyl acetate. Each extract was tested for phenolic content quantitatively using the Folin-ciocalteu reagent with gallic acid as comparison, and the final result was expressed in terms of gallic acid equivalent by spectrophotometry at a wavelength of 731.5 nm. Determination of flavonoid levels using the UV-Vis spectrophotometry method with quercetin as a comparison at a wavelength of 435 nm. The results showed that the total phenolic content of the ethanol extract was 237.0 ± 9.4% mg GAE/g and that of the ethyl acetate extract was 12.8 ± 7.7% mg, GAE/g . Flavonoid content of ethanol and ethyl acetate extracts were 30.4 ± 9.5% mg QE/g and 10.5 ± 9.1% mg QE/g, respectively. Based on this, the content of phenol and flavonoid compounds was higher in extracts with ethanol solvent than ethyl acetate solvent.